Comparative study of the anti-inflammatory, antioxidant and urease inhibitory activities of Eryngium kotschyi Boiss. and E. campestre L. var. virens (Link) Weins extracts - TAŞKIN, TURGUT (MARMARA UNIV, 2020)
Despite widespread traditional usage of Eryngium species in Anatolia (Turkey), only a limited number of scientific studies exists on E. kotschyi, an endemic species. Previously, extracts from E. campestre and E. kotschyi were reported to have significant anti-inflammatory effects in vivo. This study aimed to investigate the in vitro anti-inflammatory, antioxidant, urease inhibitory activities of ethanol extracts of E. kotschyi and E. campestre var. virens roots as well as distilled water and ethanol extracts of E. kotschyi aerial parts. The NO and cytokine inhibitory effects were evaluated by Griess and ELISA assays. The antioxidant activities were tested on DPPH center dot, ABTS center dot+ and CUPRAC assays. The EtOH extract of E. kotschyi roots (EKr EtOH) and aerial parts (EKae EtOH) inhibited 50.08% and 41.52% of NO production at 100 mu g/ml, respectively. The EtOH extract of the roots of E. campestre var. virens (ECr EtOH) and EKr EtOH provided 36.22% and 65.23% IL-6 inhibition and 44.24% and 56.84% IL-1a inhibition at 100 mu g/ml. EKae EtOH exerted highest antioxidant activity on ABTS center dot+ (2.4 +/- 0.0005 mu M trolox/mg extract) and CUPRAC (0.97 +/- 0.07 mM trolox/mg extract). This extract was also found the richest among all in terms of phenolics content (6.1 +/- 0.001 mg/GAE/g extract). EKr EtOH and ECr EtOH exhibited strongest DPPH center dot (IC50 = 1.132 +/- 0.057 mg/ml) radical scavenging and ferric reducing/antioxidant power (0.36 +/- 0.005 mM Fe2+/mg extract) activity respectively. The extracts exerted low urease inhibitory activity. Consequently, the results of this study might contribute to the elucidation of the mechanism of in vivo anti-inflammatory activity of the extracts.
Keywords: Eryngium kotschyi; Eryngium campestre var. virens; anti-inflammatory; antioxidant; urease inhibition; phenolics; NITRIC-OXIDE SYNTHASE; TRITERPENE SAPONINS; INFLAMMATORY DISEASE; CAPACITY; TURKEY; PLANTS; ROOTS; PARTS